Respuestas
Respuesta dada por:
0
remplazamos los valores
2(
-(-1)^7{3(![\frac{1}{2} )-(-1)}
<br />1-(-1)[ \frac{3}{2}+1] \frac{1}{2} )-(-1)}
<br />1-(-1)[ \frac{3}{2}+1]](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+%29-%28-1%29%7D%0A%3Cbr+%2F%3E1-%28-1%29%5B+%5Cfrac%7B3%7D%7B2%7D%2B1%5D+)
![2( \frac{3}{2}+1) 2( \frac{3}{2}+1)](https://tex.z-dn.net/?f=2%28+%5Cfrac%7B3%7D%7B2%7D%2B1%29+)
2(![\frac{3+2}{2}) \frac{3+2}{2})](https://tex.z-dn.net/?f=+%5Cfrac%7B3%2B2%7D%7B2%7D%29+)
2![( \frac{5}{2}) ( \frac{5}{2})](https://tex.z-dn.net/?f=%28+%5Cfrac%7B5%7D%7B2%7D%29+)
![\frac{10}{2}
\frac{10}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B10%7D%7B2%7D%0A+)
respuesta=5
2(
2(
2
respuesta=5
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años